Strengthening life skills : life proyect. - Medina Gómez, Alba Lorena; Mora Sarmiento, Yency Yamile (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The life project is the tool through which a medium- and long-term per- sonal plan is established, oriented to personal growth, self-knowledge and the projection of goals that generate a personal and social realization. Working on the life project from the development of skills, will allow the student to be directed to a personal realization, through their strengths, generating personal satisfaction and the satisfaction of occupying an important place in society. When such a project is established in the initial stage of the school cycle, it generates a great advantage, which guides the student to establish plans and become the executor of great projects for life, which is why this study came to life and generated a great impact in the field of application.